Anatomical characterization of the permanent human teeth that make up the incisor group - Bessone , Gabriela Guadalupe (2024)
Objectives: To identify the anatomical characteristics of human permanent natural dental pieces from the incisor group. Materials and Methods: The study was observational, descriptive, and cross-sectional. 96 incisors collected between 2015 and 2020 were analyzed, belonging to the Morphoteca of Introduction to Dentistry at the Faculty of Dentistry of the National University of the Northeast - Corrientes, Argentina. The teeth were grouped by location in the arch and observed using a metal base magnifying glass with a flexible arm, a 90 mm 3x glass lens. Digital photographic registration and anatomical description of the Upper Central Incisor (UCI), Upper Lateral Incisor (ULI), Lower Lateral Incisor (LLI), and Lower Central Incisor (LCI) were performed. The crown shape was determined through Crespi’s classification: quadrangular, trapezoidal with a larger base at the cervical, trapezoidal with a larger base at the occlusal, or ovoid. Results: Upper incisors presented a trapezoidal crown shape, taller than wide with marked development of elements on the palatal face. Single and conical root. Marked crown-root disproportion with both pieces decreasing in size distally. Lower incisors presented a quadrangular crown shape for the central and trapezoidal for the lateral, with little development of architectural elements. The crown-root ratio is balanced. Their size increases distally. Conclusions: The anatomical characterization of each dental piece in the incisor group has allowed finding characteristics that can contribute to their recognition and identification, either individually or as part of the dental system.